Success of distance learning graduates and the role of intrinsic motivation. (1st September 2020) - Simons, Joan; Leverett, Stephen; Beaumont, Kythe
ABSTRACT: This study explored the perceptions of 51 graduates of a distance learning health and social care programme, identifying what factors contributed to students continuing for the duration of their distance learning studies and completing their degree. An appreciative inquiry approach was used to identify the positive aspects of the students' experience. Support from family, tutors and employers as well as flexibility of studying at The Open University UK, enabled graduates to continue their studies. A key aspect of the graduates' success was the supportive feedback received from tutors, which they reported enabled them to build their knowledge, skills and confidence as they progressed to completion of their degree. Flexibility came in different forms, from being able to access their learning materials at any time around their busy lives, to tutors being very responsive to students' needs. The findings are discussed in relation to the students' development of competence and autonomy, factors that contribute to strengthen students' intrinsic motivation.